Improving Authentication Security by Using an Authentication Level System Model - Koivunen, Topi (My University, 2022)
The importance of the security of authentication is becoming more apparent day by day, which is why understanding different authentication methods' benefits and drawbacks is crucial when creating software. Plenty of theoretical research has been conducted on authentication, but practical applicability remains rarer. With the correct methods and tools, security by design can be achieved. Through comparative research and analysis, this thesis aims to determine a general overview on authentication methods and a model to help improve the security of an existing application's authentication scheme. Emphasis is put on the user experience in addition to the security of the software. The thesis culminates to the case study, in which we demonstrate the practical benefits of the research done for this thesis. As the result, we achieve a design and a working implementation of an improved authentication scheme to an existing application derived with the help of a level-based authentication system model. The results of the thesis show that with the correct methodology, an application's overall security can be enhanced without complicating the user experience.